A compact Bi2WO6 microflowers anode for potassium-ion storage: Taming a sequential phase evolution toward stable electrochemical cycling. (April 2021) - Zhu, Haojie; Liu, Tingting; Peng, Lu; Yao, Wentao; Kang, Feiyu; Shu, Jie; Yang, Cheng
Abstract: Potassium-ion batteries (KIBs) are considered an important alternative for lithium-ion batteries owing to the abundant potassium (K) resources and low-cost. To date, most reported anode materials for KIBs have been limited to carbonaceous materials which can well accommodate the large potassium ions (K + ) but show humble capacity performance. As compared, metal oxide-based anodes can potentially provide higher capacity yet cyclability is poor, which has been rarely researched. Herein, we report a sequential phase evolution mechanism for bimetallic oxide anode. Upon potassiation, the microflower-like Bi2 WO6 undergoes a multistep evolution process, which first combines with K + then converts into a highly reversible phase of Bi, then via a solid-solution reaction eventually it forms the K3 Bi alloy. After repeated cycling process, such unique hierarchical and mesoporous morphology of Bi2 WO6 can be well maintained, leading to superior cyclability with a high specific potassium storage capacity (652 mAh g −1 at 100 mA g −1 ). Even at a large current density of 1 A g −1, a reversible specific capacity of 216 mAh g −1 can still be delivered over 300 cycles. Such a novel working mechanism of bimetallic oxide anodes will promote the practical use of KIBs in diverse energy storage applications. Graphical Abstract: ga1 Highlights: A novel sequential phase evolution mechanism for KIBs. The unique highly reversible series transition reactions from Bi2 WO6 to Bi-K alloy. Self-assembled interlaced microflower-like Bi2 WO6 anodes are prepared by hydrothermal method. Structural evolution is analyzed by in-situ XRD and ex-situ TEM. At a current density of 1 A g −1, a reversible capacity of 216 mAh g −1 over 300 cycles is still delivered.